Implementation Of Direct Instruction In Snack Bouquet Training At Baitul Hikmah - Fikka Izza Dinillah; Sri Handajani (Jurnal Pendidikan Tata Boga dan Teknologi, 2025)
This study aims to examine the implementation of the Direct Instruction model in snack bouquet training at Pondok Pesantren Baitul Hikmah. The research uses a descriptive quantitative approach with data collected through observation, practice, and questionnaires. The subjects of this study were 15 female students who participated in the training. The Direct Instruction model was applied through systematic stages, including the introduction, core activities, and closing. The results show that the instructor's activities at each stage of the training received a "very good" category. In addition, the participants showed active involvement and positive responses during the training. This training proved effective in enhancing the participants’ creativity in independently and innovatively creating snack bouquets. Therefore, the Direct Instruction method is effective for practical skill-based training such as snack bouquet making.